No end in sight the continuing menace of nuclear proliferation - Busch, Nathan E. (Manas, 2005)
'No End in Sight' provides the most comprehensive and up-to-date analysis of issues at the forefront of contemporary international affairs. The book weights the risks and benefits, both current and potential, of further nuclear proliferation while offering clear policy recommendations based on the author's careful scrutiny of modern global politics. In this era, in which both terrorists and aggressive nation-states can devastate millions of people, Busch's insights and conclusions will prove critical to understanding the implications of nuclear proliferation.